The Influence of Trust in Management, Goal Clarity, and Work-Family Conflict on Intention to Stay with the Mediation of Work Engagement Among Employees of PT. Sanyon Bangun Lestari - Kevin Prilian; Oloan Situmorang (Green Publisher Indonesia, 2024)
An effort to maintain employee engagement is one of the major challenges for organizations currently because companies that are engaged in the construction industry must be able to overcome every obstacle, such as increased competition, decreased purchasing power, and instability in raw material prices, when carrying out their business activities, so companies have an urgency in maintaining the best talent over the long term as an effort to increase their competitive advantages in the organization. This study aims to fill the research gap by testing the influence of trust in management, goal clarity, and work-family conflict on employees’ intention to stay by involving work engagement as a mediator, especially in every company that is engaged in the construction industry. Data were collected through a structured questionnaire from 51 employees who worked as non-managerial staff at PT. Sanyon Bangun Lestari, in Indonesia, as one of the companies that are engaged in the construction industry. This study used a quantitative approach, so the data were analyzed through partial least squares with structural equation modelling when measuring a construct. The results of this study indicate that trust in management and work engagement have a positive and significant impact on intention to stay, whereas work engagement plays an important role in mediating the influence of trust in management and goal clarity on intention to stay. It is hoped that this study can be a reference in the development of future studies, especially research that utilizes different objects and variables.